America and the sea (Univ. of Georgia, 1995)
This is the first literary history of the United States to explore exclusively the presence of the sea in American writing. A multiauthor work, it covers the periods and genres that make up our national literature as it considers the ubiquity of nautical symbols, images, and figurative language in addition to expressions of the sea experience itself. While this book situates the literature within American history, particularly maritime history, a chapter on hymns, chanteys, and sea songs as well as an annotated portfolio of American seascape art expand and enrich the literary and cultural contexts The book's fourteen chapters consider the written presence of the Atlantic, the Pacific, and the Gulf of Mexico, and also move inland to address the literature of the Great Lakes. They reveal the importance of the sea in works by women, African Americans, and Native Americans - which is one aspect of the book's special considerations not only of race and gender but also of genre, religion, class, audience, aesthetics, tradition, and innovation. Written in a style accessible to a broad, diversely educated audience, and featuring extensive bibliographies essential to further reading and research, America and the Sea is a unique work on an abiding presence in our cultural consciousness. In addition, its collaborative scholarship seeks to provide wider historical and cultural frameworks for understanding texts, enlarging traditional canons, and making strong use of cross-disciplinary study
Keywords: Aufsatzsammlung; Engels; Letterkunde; Zeeën; Englisch; Literatur; American literature; Explorers in literature; Geographical discoveries in literature; Ocean travel in literature; Sea poetry; American; Sea stories; American; Seafaring life in literature; Meer